The communication style of Prof. Dr. M. Quraish Shihab, M.A., and K.H. Ahmad Bahauddin Nursalim in interpreting the Quran (Study on YouTube channel of Pusat Studi Al-Quran) - Samsuriyanto Samsuriyanto; Moh Saifulloh; Zainul Muhibbin (Priviet Social Sciences Journal, 2025)
Prof. Dr. M. Quraish Shihab, M.A., is a scholar born from the habaib tradition and accepted by the pesantren tradition. While K.H. Ahmad Bahauddin Nursalim is a scholar born from pesantren tradition and accepted by the habaib tradition. This study aims to describe the communication of Prof. Dr. M. Quraish Shihab, M.A., and K.H. Ahmad Bahauddin Nursalim in Interpreting the Quran which was uploaded through the YouTube channel of Pusat Studi Al-Quran. This study used a media text analysis with a critical approach. The results of this study show that Prof. Dr. M. Quraish Shihab, M.A., has a polite communication style and K.H. Ahmad Bahauddin Nursalim has a humorous communication style in interpreting the Quran. Second, Prof. Dr. M. Quraish Shihab, M.A., emphasized the message of “imitating the Prophet in life” and K.H. Ahmad Bahauddin Nursalim emphasized the message of “Happy life”. Third, YouTube channel of Pusat Studi Al-Quran as a communication media that displays a YouTube Program entitled “Maulid Nabi Muhammad SAW 1447 H Bersama Gus Baha dan Prof. Quraish Shihab” on Saturday, November 1, 2025. Fourth, the communication of Prof. Dr. M. Quraish Shihab, M.A., and K.H. Ahmad Bahauddin Nursalim received a response in the form of views that were much larger than the number of subscribers, getting likes that almost equaled the number of subscribers and reaching almost 400 comments. Fifth, netizen comments as communication feedback in the form of netizen reviews of Prof. Dr. M. Quraish Shihab, M.A. ’s appreciation to K.H. Ahmad Bahauddin Nursalim and netizen admiration for Prof. Dr. M. Quraish Shihab, M.A., and K.H. Ahmad Bahauddin Nursalim. And, the effect of the interpretation of the Quran as a communication effect has three effects, namely cognitive effect, affective effect and behavioral effect. This research is important to obtain a description of the communication of Prof. Dr. M. Quraish Shihab, M.A., and K.H. Ahmad Bahauddin Nursalim in Interpreting the Quran which was uploaded through the YouTube channel of Pusat Studi Al-Quran.